ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PT SENTUL CITY Tbk PERIODE 2014-2018 - Amaroh, Rakhmi; Apriani, Herlina (Economicus, 2021)
The data analysis technique uses financial ratio analysis which includes liquidity ratios, profitability ratios, solvency ratios and activity ratios. The results showed that the financial performance of PT Sentul City Tbk for the 2014-2018 period tended to be in bad shape. Based on the Liquidity Ratio (Current Ratio, Quick Ratio, and Cash Ratio) it is stated that it is not good because the ratio value is below the industry average standard. Based on the Profitability Ratio Net Profit Margin is declared good because the ratio value is above the industry average standard, while the Return on Equity is declared not good because the ratio value is below the industry average standard. Based on the Solvency Ratio (Debt to Asset Ratio and Debt to Equity Ratio) it is declared good because the ratio value is below the industry average standard. Based on the ratio of activities (Fixed Assets Turn Over and Total Assets Turn Over) it is declared not good because the ratio value is below the industry average standard.